Your memory - "Baddeley, Alan" (New Delhi, 1996)
Do you want to stop forgetting appointments, birthdays, and other important dates? Work more efficiently at your job? Study less and get better grades? Remember the names and faces of people you meet? The good news is that it's all possible. Your Memory will help to expand your memory abilities beyond what you thought possible. Dr. Higbee reveals how simple techniques, like the Link, Loci, Peg, and Phonetic systems, can be incorporated into your everyday life and how you can also use these techniques to learn foreign languages faster than you thought possible, remember details you would have otherwise forgotten, and overcome general absentmindedness. Higbee also includes sections on aging and memory and the latest information on the use of mnemonics.
Keywords: Psychology